تأثیر استخدام وسائل لعبة المنوبولي ( Monopoli ) لتطوّر كفاءة المفردات الطلاب - Hanifah, Umi; Mudlofir, Ali; Izzah, Athiyyatul; Zahroh, Nadiya Iffatus (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
This study aims to determine the extent to which students’ mastery of mufradat is increased by using a monopoly game. This research includes field research that uses qualitative methods, namely methods that focus on in-depth observations. Monopoly games can improve students’ mastery of mufradat. Researchers use Monopoly games in teaching vocabulary to ask students to have the desire and enthusiasm to teach Arabic, and he can improve language skills through the large number of vocabulary students have.